SDG12 - sustainable consumption and production : a revolutionary challenge for the 21st century - Bernstein, Jennifer Moore; Vos, Robert O. (Emerald Publishing Limited, 2021)
This book takes a wide-ranging and non-dogmatic view of SDG12, tackling various approaches as to how production and consumption can provide for human well-being while minimizing destructive effects on the biophysical environment. With chapters focusing on circular economies, product accounting systems, and sustainable procurement, this volume presents technical information in an accessible way and provides a much-needed overview of activity and approaches to achieving the development goal. The authors provide a thorough understanding of the history and effectiveness of SDG 12 by juxtaposing competing theories of sustainable production and consumption, from critics who advocate a "degrowth" agenda to explicitly neo- liberal approaches. They also examine the underlying contradictions in these theories and the degree to which these competing approaches can complement one another.
Includes index.
Keywords: Sustainable Development Goals.; United Nations.; Sustainable development.; Business & Economics -- Development -- Sustainable Development.; Sustainability.; elektronické knihy; electronic books